Decision Support System for Assessment of Learning Process Using Simple Additive Weighting - Euis Nurninawati; Henderi Henderi; Sudaryono Sudaryono (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
Lecturers are entitled to get promotions and awards in accordance with their academic performance. Service of teaching and learning process of quality and professional will affect hope and feeling of satisfaction for student to spirit in follow lecture. Performance appraisal according to the favorite lecturer selection guidelines are (a) giving the syllabus at the beginning of the semester, (b) teaching on time, (c) mastering the taught material, (d) correcting assignments and timely grades and (e) serving academic guidance students well. Lecturers who can be elected are a lecturer who have given lectures on all courses in the department at least two semesters and are not currently following the learning task and has provided academic guidance services at least two semesters. Because there is no objective method to decide better and faster, based on existing data. Making the information system that can provide recommendations needed a proper method of decision making. Simple Additive Weighting (SAW) method is appropriate for the decision-making process because it can determine the weight value for each attribute, then proceed to the ranking process that will select the best alternative from some of the best alternatives.